Canine inflamed nonepitheliotropic cutaneous T‐cell lymphoma: a diagnostic conundrum. Issue 1 (19th January 2013) - Moore, Peter F.; Affolter, Verena K.; Keller, Stefan M.
Abstract : Background – Cutaneous T‐cell lymphoma (CTCL) in dogs is a heterogeneous disease complex, which consists of nonepitheliotropic (NE) and epitheliotropic forms. These lymphomas are readily recognized by the presence of dominant populations of cytologically atypical lymphocytes. Objective – The objective of this study was to introduce the key features of inflamed NE‐CTCL, which is easily confused with reactive, inflammatory histiocytic disease. Animals – Twenty‐four dogs (mean age 7.5 years) presented with inflamed NE‐CTCL. Lesions presented as nodules, plaques or masses. An initial diagnosis of cutaneous reactive histiocytosis (11 dogs) or histiocytic neoplasia (three dogs) was made by primary pathologists. Methods – Lesions were assessed by histology and immunohistochemistry to detect canine leukocyte antigens. Lesional genomic DNA was extracted and gene rearrangement analysis of the T‐cell receptor γ locus was assessed. Results – The cutaneous lesions consisted of pleocellular infiltration of the dermis with variable extension into the subcutis. The lesions often surrounded vessels and adnexae. Epitheliotropism was minimal or lacking. Small lymphocytes, plasma cells and intermediate to large, cytologically atypical lymphocytes were scattered between prominent histiocytic infiltrates. Atypical lymphocytes often had marked variation in the intensity of CD3 expression. Molecular clonality analysis of the T‐cell receptor γ locus revealed clonal expansion of T cells in 22 of 23 dogs tested. Conclusion – The recognition of inflamed NE‐CTCL and its differentiation from cutaneous reactive histiocytosis depends on careful assessment of lymphocyte morphology and immunostaining patterns. Confirmation of the diagnosis is best accomplished by T‐cell antigen receptor gene rearrangement analysis.